1995
DOI: 10.1007/bf01499074
|View full text |Cite
|
Sign up to set email alerts
|

Effects of inconsistent eyewitness statements on mock-jurors' evaluations of the eyewitness, perceptions of defendant culpability and verdicts.

Abstract: In attempting to discredit an eyewitness, it is a common strategy for an attorney to highlight inconsistencies in the eyewitness's recall testimony during cross-examination and encourage the jurors to infer, based on those inconsistencies, that the eyewitness's memory is faulty. An experiment was conducted to examine the effectiveness of this cross-examination strategy. Subjects viewed a simulated cross-examination and rendered judgments about the eyewitness and defendant. The type of inconsistent testimony wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

14
87
0

Year Published

1999
1999
2017
2017

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 96 publications
(101 citation statements)
references
References 13 publications
14
87
0
Order By: Relevance
“…Because eyewitnesses are often required to complete multiple interviews prior to their in-court appearance, concerns regarding the credibility of the witness accounts can arise when the witness changes his/her memory reports across interviews (e.g., when the witness recalls that the perpetrator was wearing a red shirt during one interview and then recalls that the perpetrator was wearing a gray shirt during a subsequent interview). Mock jurors judge inconsistent witnesses as less credible than consistent witnesses (Berman, Narby, & Cutler, 1995;Brewer & Burke, 2002;Pozzulo & Dempsey, 2009). …”
Section: Context Of Resmentioning
confidence: 99%
“…Because eyewitnesses are often required to complete multiple interviews prior to their in-court appearance, concerns regarding the credibility of the witness accounts can arise when the witness changes his/her memory reports across interviews (e.g., when the witness recalls that the perpetrator was wearing a red shirt during one interview and then recalls that the perpetrator was wearing a gray shirt during a subsequent interview). Mock jurors judge inconsistent witnesses as less credible than consistent witnesses (Berman, Narby, & Cutler, 1995;Brewer & Burke, 2002;Pozzulo & Dempsey, 2009). …”
Section: Context Of Resmentioning
confidence: 99%
“…Similarly, Lagnado and Harvey (2008) argue that when performing complex reasoning tasks where not all evidence point in the same direction, people group the evidence into different coherent sets as a basis for further consideration. In related studies it has been concluded that, if an individual witness delivers inconsistent testimonies, then subjects will assign her a lower degree of credibility; and it has been observed that inconsistency leads to lower rates of conviction (see, e.g., Berman and Cutler 1996;Berman, Narby and Cutler 1995). Finally, Brewer et al (1999) present evidence supporting the claim that perceived witness credibility is positively affected by consistency between reports from different witnesses, albeit to a lesser extent than intra-witness consistency.…”
Section: Introductionmentioning
confidence: 65%
“…Since all inconsistencies are from plaintiff's witnesses, and since jurors tend to view inconsistency as a proxy for inaccuracy (although most research on the testimonial inconsistency/inaccuracy relationship has revolved around eyewitness identifications [Berman & Cutler, 1996;Berman, et al, 1995;Brewer & Burke, 2002;Wells, Olson, & Charman, 2002]), the plaintiff's case against the defendant should be viewed as being weaker by those participants in uncertain emotional states. Because they will have an affirmative, demonstrable basis for verdicts in favor of the defendant, it is predicted that participants in uncertain emotional states who read the inconsistent transcripts will have the highest degree of confidence in their verdict.…”
Section: Verdict Confidence As a Results Of Processing Stylementioning
confidence: 99%
“…Prior research on the effects of inconsistent testimony by eyewitnesses has found that exposing mock jurors to different levels of inconsistency (new testimony offered during the trial which was not disclosed during any investigation, contradictions between pretrial assertions and in-court testimony, and inconsistent statements within trial testimony), no matter how diagnostic the content, any exposure to inconsistent eyewitness testimony reduced likelihood of conviction, degree of defendant guilt, and eyewitness credibility (Berman & Cutler, 1996). Similarly, Berman, Narby, and Cutler (1995) found that with regard to eyewitness testimony, any inconsistent statements by the witness having to do with their view of the perpetrator, whether perceptually central (i.e., having to do with the perpetrator's appearance) or perceptually peripheral (i.e., having to do with information irrelevant to the accuracy of a personal identification, such as nearby objects) in nature, resulted in lower ratings of defendant culpability and lower ratings of eyewitness credibility by mock juror participants, while those participants who were exposed to eyewitnesses making inconsistent statements regarding perceptually central details convicted the defendant at a lower rate. However, these distinct effects of inconsistencies focused on central and/or peripheral details of perception and not central and/or peripheral details in terms of relevance to legal decision-making or any probative value, so it is possible that the overall legal relevance of the inconsistencies themselves may explain why I did not find what I had expected to find.…”
Section: Methodological Explanationsmentioning
confidence: 99%
See 1 more Smart Citation